The Role of Gasotransmitters in Gut Peptide Actions - Verbeure, Wout; van Goor, Harry; Mori, Hideki; van Beek, André P.; Tack, Jan; van Dijk, Peter R. (Frontiers in Pharmacology, 2021)
Although gasotransmitters nitric oxide (NO), carbon monoxide (CO) and hydrogen sulfide (H2S) receive a bad connotation; in low concentrations these play a major governing role in local and systemic blood flow, stomach acid release, smooth muscles relaxations, anti-inflammatory behavior, protective effect and more. Many of these physiological processes are upstream regulated by gut peptides, for instance gastrin, cholecystokinin, secretin, motilin, ghrelin, glucagon-like peptide 1 and 2. The relationship between gasotransmitters and gut hormones is poorly understood. In this review, we discuss the role of NO, CO and H2S on gut peptide release and functioning, and whether manipulation by gasotransmitter substrates or specific blockers leads to physiological alterations.